Comparing Resource Use in Medical Admissions of Children With Complex Chronic Conditions - Silber, Jeffrey H; Rosenbaum, Paul R; Pimentel, Samuel D; Calhoun, Shawna; Wang, Wei; Sharpe, James E; Reiter, Joseph G; Shah, Shivani A; Hochman, Lauren L; Even-Shoshan, Orit (Medical care, 2019)
Children with complex chronic conditions (CCCs) utilize a disproportionate share of hospital resources. We asked whether some hospitals display a significantly different pattern of resource utilization than others when caring for similar children with CCCs admitted for medical diagnoses. Using Pediatric Health Information System data from 2009 to 2013, we constructed an inpatient Template of 300 children with CCCs, matching these to 300 patients at each hospital, thereby performing a type of direct standardization. Children with CCCs were drawn from a list of the 40 most common medical principal diagnoses, then matched to patients across 40 Children's Hospitals. Rate of intensive care unit admission, length of stay, resource cost. For the Template-matched patients, when comparing resource use at the lower 12.5-percentile and upper 87.5-percentile of hospitals, we found: intensive care unit utilization was 111% higher (6.6% vs. 13.9%, P<0.001); hospital length of stay was 25% higher (2.4 vs. 3.0 d/admission, P<0.001); and finally, total cost per patient varied by 47% ($6856 vs. $10,047, P<0.001). Furthermore, some hospitals, compared with their peers, were more efficient with low-risk patients and less efficient with high-risk patients, whereas other hospitals displayed the opposite pattern. Hospitals treating similar patients with CCCs admitted for similar medical diagnoses, varied greatly in resource utilization. Template Matching can aid chief quality officers benchmarking their hospitals to peer institutions and can help determine types of their patients having the most aberrant outcomes, facilitating quality initiatives to target these patients.